2016
DOI: 10.35724/jies.v7i2.506
|View full text |Cite
|
Sign up to set email alerts
|

Interaksi Komitmen Organisasi Terhadap Faktor-Faktor Yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah

Abstract: Audit BPK for the financial statements 2013 of Merauke district received a qualified opinion. This means that there are other things that should be repaired in the preparation of financial statements. Therefore, this study aimed to determine the effect of the competence of the Human Resources and internal control system to the quality of financial reports of local government, and the moderating influence of organizational commitment on the relationship between HR competencies and internal control system to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 1 publication
2
5
0
7
Order By: Relevance
“…Based on statistical tests and significance it is identified that there is a positive but not significant effect between organizational commitment and the quality of financial reporting. This is in accordance with the results of Septarini and Papilaya's research [18] on the interaction of organizational commitment to the factors that influence the quality of local government financial statements, which explains that organizational commitment strengthens the relationship of Human Resources competencies to the Quality of Financial Statements, and concludes that organizational commitment moderates the relationship between competencies of human resources to the quality of local government financial statements.…”
Section: Organizational Commitment On Quality Of Financial Reportingsupporting
confidence: 89%
“…Based on statistical tests and significance it is identified that there is a positive but not significant effect between organizational commitment and the quality of financial reporting. This is in accordance with the results of Septarini and Papilaya's research [18] on the interaction of organizational commitment to the factors that influence the quality of local government financial statements, which explains that organizational commitment strengthens the relationship of Human Resources competencies to the Quality of Financial Statements, and concludes that organizational commitment moderates the relationship between competencies of human resources to the quality of local government financial statements.…”
Section: Organizational Commitment On Quality Of Financial Reportingsupporting
confidence: 89%
“…The Village Government of Bantul is required to use information technology in managing funds as a transparent village. It is in line with [38], stating that the roles and policies taken by top management are very decisive because every job performed by subordinates only follows what the superiors' order.…”
Section: Influences Of Organizational Commitment On the Relationship ...supporting
confidence: 67%
“…Apabila sumber daya manusia yang digunakan berkompeten dan memiliki komitmen organisasi yang tinggi, maka dia akan senang dalam bekerja, sehingga akan menggunakan sepenuhnya pengetahuan, pengalaman dan pemahamannya tentang ilmu akuntansi dalam menjalankan tugas dan tanggung jawabnya, sehingga laporan keuangan yang dihasilkan lebih dapat diandalkan (Septarini & Papilaya, 2016). Penelitian (Lestari & Dewi, 2020) menunjukkan hasil penelitian bahwa pemahaman akuntansi berpengaruh signifikan terhadap kualitas laporan keuangan.…”
Section: Pemahaman Akuntansi Memoderasi Komitmen Organisasi Terhadap ...unclassified